Czynności mowy, które budują złe relacje międzyludzkie (na podstawie współczesnych sporów publicznych) = Speech acts that build up bad human relationships (based on contemporary public disputes) - Kaczor, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to discuss what is important for language users when during a discussion they employ specific speech acts which determine the ethics of interpersonal communication. Important are also aspects of speaking, rules and ways of behaving as well as a common value system they are based on, which in the public disputes discussed in the study turned out to be disrupted.
Keywords: czynności mowy; komunikowanie; kontakty językowe; kultura języka; spory publiczne; speech acts; communication; language contacts; culture of language; public disputes